Chapter Employability as a Global Norm: Comparing Transnational Employability Policies of OECD, ILO, World Bank Group, and UNESCO - Singh, Shalini (Studies on Adult Learning and Education, 2020)
This article analyses transnational policies on employability to understand the development of employability as a global norm and reflects about its consequences for stakeholders in the field of lifelong learning.